Physical qualification of school-leavers with different level of professional readiness and somatotypes at the stages of studying in the military institution of higher education of the forces of civil defence - Gonshovsky V. (Kharkov National Pedagogical University, 2010)
The dynamics of indexes of physical preparedness of rescuers is considered with the different levels of professional readiness and somatotypes. Probed 79 students. Formed battery from 14 tests. Professional readiness of graduating students was determined on results state examinations. Considerable divergences are exposed between excellent student and students with the lower levels of professional readiness. The necessity of account of these excellent student is rotined at forming of optimum maintenance of physical preparation.